ANALISIS FAKTOR SITUASI YANG MEMPENGARUHI PEMILIHAN PASAR TRADISIONAL DAN PASAR MODERN DI KOTA PONTIANAK - Santika, Dewi (MABIS, 2013)
In this recent years, the growth of modern market in Pontianak city are rapidly. Its drive by the growth of new residence area and develop of customer preference. Therefore the tradition market also didnât leave by its customer. By this fenomena, the writer in thisÂ esearch wants to find the situation factor that drive consumer to decided both traditional and modern market. This research used descriptive research and the research methods were survey method. The sampling involves 50 customers which ever visit and do transaction in both traditional market and modern market by using accidental sampling method. Data collection techniques used was interview, questioner, and bibliography study. Data analysis technique used in this research was qualitative analysis technique. It is concluded that customer will choose traditional market if they want to gets fresh, cheap, variety goods and social needs. But they will choose modern market if they have limited time for purchasing, convineance and more welcome services.